DRESS SYNDROME DEMYSTIFIED: INSIGHTS FROM A PATHOLOGIST’S PERSPECTIVE - sakshi sakshi agrawal; Dr. Priyanka Patil (Tropical Journal of Pathology and Microbiology, 2024)
Background: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a constellation of symptoms that manifest because of certain medications. Several antipsychotics, antibiotics, anti convulsants, and sulfa-containing drugs are known to be implicated in the etiology of DRESS syndrome. It is a severe idiosyncratic drug reaction with a long latency period and due to the asymptomatic beginning and non-specific nature of symptoms, it is difficult to identify. This disease is diagnosed using the RegisCAR (European Registry of Severe Cutaneous Adverse Reaction) scoring system.The clinical presentation of this disorder consists of a diffuse rash, lymphadenopathy, and systemic organ damage. The diagnostic workup comprises of monitoring inflammatory markers on laboratory work, and a skin biopsy (to assess the etiology of the rash).Case presentation: A 24-year-old male presented with complaints of skin lesions over whole body for the past 15 days along with erythematous lesions with exfoliation and scaling. Conclusion: The reported case emphasizes the importance of thorough medical history including drug reactions in differential diagnosis.The causative drug in this case was found to be antibiotics (cefexime). The treatment for the same is withdrawal of causative drug and using corticosteroids, in this patient dexamethasone was used.